2013
DOI: 10.1002/ece3.839
|View full text |Cite
|
Sign up to set email alerts
|

Projected marine climate change: effects on copepod oxidative status and reproduction

Abstract: Zooplankton are an important link between primary producers and fish. Therefore, it is crucial to address their responses when predicting effects of climate change on pelagic ecosystems. For realistic community-level predictions, several biotic and abiotic climate-related variables should be examined in combination. We studied the combined effects of ocean acidification and global warming predicted for year 2100 with toxic cyanobacteria on the calanoid copepod, Acartia bifilosa. Acidification together with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 51 publications
3
60
1
Order By: Relevance
“…More recent work continues to strongly support the findings of AR5 that many species are undergoing geographical and phenological shifts as a result of warming (Vehmaa et al, 2013;Goberville et al, 2014;Kamya et al, 2014;Mackenzie et al, 2014a;Church et al, 2013;Mackenzie et al, 2014a,b,c;Queirós et al, 2014;Rice et al, 2014). The AR5 found that zooplankton have exhibited some of the most extreme geographic range shifts of over 100 km decade −1 .…”
Section: Updates To Ar5supporting
confidence: 52%
See 3 more Smart Citations
“…More recent work continues to strongly support the findings of AR5 that many species are undergoing geographical and phenological shifts as a result of warming (Vehmaa et al, 2013;Goberville et al, 2014;Kamya et al, 2014;Mackenzie et al, 2014a;Church et al, 2013;Mackenzie et al, 2014a,b,c;Queirós et al, 2014;Rice et al, 2014). The AR5 found that zooplankton have exhibited some of the most extreme geographic range shifts of over 100 km decade −1 .…”
Section: Updates To Ar5supporting
confidence: 52%
“…Synergistic negative effects have been observed on the growth, survival, fitness, calcification and development of organisms (Padilla-Gamino et al, 2013;Vehmaa et al, 2013;Gaitán-Espitia et al, 2014;Gobler et al, 2014;Hyun et al, 2014;Mackenzie et al, 2014b;Madeira et al, 2014;Maugendre et al, 2014Roy et al, 2014;Schram et al, 2014;Rosa et al, 2014a,b;Schmidt et al, 2014a). In some cases, hypoxic conditions have been observed to mediate the negative effects of ocean acidification (Mukherjee et al, 2013).…”
Section: Updates To Ar5mentioning
confidence: 99%
See 2 more Smart Citations
“…The current ocean acidification and change in the equilibrium of the seawater chemistry are so rapid that they will most likely lead to major changes in marine ecosystems and impact marine life (Pelejero et al, 2010). For more than a decade, the biological responses of phytoplankton (Lohbeck et al, 2012), foraminifera (Bijma et al, 2002), pteropods (Bednaršek et al, 2017), bivalves (Jansson et al, 2013), crustaceans (Vehmaa et al, 2013) and fish (reviewed by Clements and Hunt, 2015;Esbaugh, 2017) have been studied under different ocean acidification scenarios. Research suggests that mobile species, such as crustaceans and fish are less sensitive to acidification than sessile species, possibly due to their high metabolic rates and active regulation of internal pH (reviewed by Kroeker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%